2022
DOI: 10.26434/chemrxiv-2022-7hq66
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radical-Polar Crossover Catalysis with a d0 Metal Enabled by a Redox-Active Ligand

Abstract: Radical-polar crossover mechanisms are invoked in numerous late transition metal and photocatalyzed reactions. To the best of our knowledge, reductive radical-polar crossover mechanisms are not invoked for group 3 early transition metals due to their propensity to exist in high oxidation states. Through use of a redox-active (tris)amido ligand we have accessed this mechanism for use with early transition metals. This mechanism is showcased through enabling product formation for a wide variety of elimination pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition to accessing cross-coupling catalysis with these complexes via a one-electron pathway, we recently reported that the two-electron chemistry of the tris(amido) ligand in 1-Sc is also accessible for catalysis. 42 This was demonstrated through the ability of complex 1-Lu to perform radical-polar crossover catalysis via the formation of gem-difluoroalkenes from α-CF 3 benzylic bromide substrates. The proposed mechanism for this reaction involves two sequential oneelectron oxidations of the complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to accessing cross-coupling catalysis with these complexes via a one-electron pathway, we recently reported that the two-electron chemistry of the tris(amido) ligand in 1-Sc is also accessible for catalysis. 42 This was demonstrated through the ability of complex 1-Lu to perform radical-polar crossover catalysis via the formation of gem-difluoroalkenes from α-CF 3 benzylic bromide substrates. The proposed mechanism for this reaction involves two sequential oneelectron oxidations of the complex.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We were also interested to see if Lu could participate in two-electron redox chemistry as was recently reported with 1-Sc (Figure 1b). 42 For this study, we chose to investigate lutetium since it is a diamagnetic lanthanide. Additionally, its propensity to exist as Lu(III) is similar to how Sc and Y primarily exist as M(III).…”
mentioning
confidence: 85%